PROSES PENILAIAN KINERJA TERHADAP KEPUASAN KERJA DENGAN KEPUASAN UMPAN BALIK KINERJA SEBAGAI VARIABEL MEDIASI PADA PEGAWAI PERGURUAN TINGGI DI CEPU - Fitriana Oktavianti (Journal of Business & Banking, 2012)
This study attempts to describe the effect of Performance Appraisal Process Factors on Job Satisfaction with Performonce Appraisal Feedback Satisfaction as intervening variable. The data which were taken in this study were the employees of Higher Education in Cepu, Central of Java. The survey was employed on the responses from 81 employees of teachings staff and administration staff, The results show that the performance ratings, satisfaction with performance appraisal, satisfaction with performance appraisal system and satisfaction with performance appraisal feedback all have significant coruelation toward job satisfaction. In addition, Performance Rating, and Satisfaction with Performance Appraisal System have positive correlation toward job satisfaction, but satisfaction with rater and performance appraisal system has no significant correlation toward job satisfaction. Thus, it can be concluded that satisfaction with performance appraisal feedback was used only by intervening variable in the relations of satisfaction with rater to job satisfaction variable and satisfaction with performonce appraisal system to job satisfaction.